IDENTIFIKASI UNSUR TANAH LITOSOL DENGAN METODE XRF (X-RAY FLUORESCENCE) DAN FTIR (FOURIER TRANSFORM INFRA RED) BERDASARKAN TITIK ELEVASI DI DESA SAMANGKI KECAMATAN SIMBANG KABUPATEN MAROS - Andi Syam Rizal; Minarti Minarti; Abdul Munim Thariq; Nurhafida Turayni; Jumardin Jumardin; Wahyullah Wahyullah (Program Studi Pendidikan Fisika FKIP Universitas Muslim Maros, 2023)
XRF method to determine elemental content and FTIR test to determine the nature of chemical compounds (functional groups) of Litosol soil at the slope (elevation angle) and the distance of the research trajectory lines. The identified elemental levels are Fe, Si, Ti, K, Mn and Ca. Fe represents the highest elemental content value for each research path. Fe for paths (1-2) are 23.82 % and 37.69%, tracks (5-6) are 23.11% and 37.47%, and paths (9-10) are 40.44% and 33.99% at different elevation angles. The lowest element level is Ca. The value of Ca for each track is 0.24% and 0.66% (1-2), 0.28% and 0.30% (5-6) and 0.27% and 0.62% (9-10) for each different elevation angle. The FTIR method to determine functional groups (chemical compounds) uses the same parameters as the XRF method. The O-H functional groups were detected at wave numbers 3698.31 cm-1 and 3620.34 cm-1 with the theoretical accuracy ranges of 3700-3000 cm-1 and 3590-3650 cm-1. The C=C which is a double bond functional group was detected at wave number 1640.8 cm-1 in the theoretical range of 1610-1680 cm-1. The C-H functional group on each track was detected in three different types of wave numbers with values of 908.99 cm-1, 786.86 cm-1 and 746 cm-1, respectively. The range of wave number accuracy for C-H is 690-900 cm-1.